Pengaruh Harga dan Lokasi terhadap Keputusan Pembelian di Nine Aces Pool and Cafe Kota Bandung - Muhammad Fareeka (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study analyzes the effect of price and location on consumer purchase decisions at Nine Aces Pool and Cafe in Bandung City. The research was motivated by intense competition in Bandung's culinary sector, where affordability and accessibility play decisive roles in shaping consumer preferences. A quantitative approach was used with a survey method involving 96 respondents selected from a population of 2,171 consumers using the Lemeshow formula and proportionate stratified random sampling. Data were collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The findings indicate that both price and location have significant partial and simultaneous impacts on purchase decisions. Location proved to be the dominant factor influencing consumer behavior, suggesting that strategic positioning and convenient accessibility are more influential than pricing alone. The study recommends that management optimize pricing strategies and enhance location-related facilities to strengthen customer loyalty and satisfaction.